Rice Science: Biotechnological and Molecular Advancements - Verma, Deepak Kumar; Srivastav, Prem Prakash; Nadaf, Altafhusain B.; Apple Academic Press (Toronto ; New Jersey : Apple Academic Press, 2018)
A significant crop in our global society, rice is a staple food product for over half of the world$1 (Bs population. New technologies are being researched and utilized for increasing the overall production of strong rice crops throughout the world. This book focuses on the new areas of research on the most recent biotechnological and molecular techniques to aid in this endeavor. The researchers who have contributed to this compendium are international leaders in their respective fields. The original research included in the volume is strengthened through the addition of surveys, reviews, success stories, and other aspects that impact the global agricultural industry.s
Emerging Trends of A20/AN1 Zinc-Finger Proteins in Improving Rice Productivity Under Abiotic Stress -- Subramanian Radhesh Krishnan, Pandiyan Muthuramalingam, Chakravarthi Mohan, and Manikandan Ramesh -- Potent Avenues for Conferring Salinity Tolerance in Rice -- Tushar Khare and Vinay Kumar -- Salt Stress Responses of Glycophytic Rice and Halophytic Rice: Physiological, Biochemical, and Molecular Aspects -- Deepak Shelke, Ganesh Nikalje, and Parmeshwar Kumar Sahu -- Technological Development for Abiotic Stress (AbS) in Rice -- Pandiyan Muthuramalingam, Subramanian Radhesh Krishnan, Deepak Kumar Verma, and Manikandan Ramesh -- Assessment of Aromatic Content and In-Vitro Responses in Traditional Indian Rice Varieties -- Srinivasan Balamurugan, Shanmugaraj Bala Murugan, Inchakalody P. Varghese, Ashwini Malla, Kantilal V. Wakte, Sarika Mathure, Altafhusain B. Nadaf, and Ramalingam Sathishkumar -- Biochemical Evaluation of Irrigated Flooded Transplanted and Aerobic Rice (Oryza sativa L.): A Review -- Manisha Kumari, Bavita Asthir, Deepak Kumar Verma, and Vishal Singh -- Agrobacterium-Mediated Genetic Transformation Practices for Improvement of Rice Quality and Production -- Aziz Ahmad -- Molecular Markers and Marker Assisted Selection (MAS) Towards Yield and Quality Improvement in Rice -- Rukmini Mishra, Jatindra Nath Mohanty, Deepak Kumar Verma, Raj Kumar Joshi, and Prem Prakash Srivastav -- The CRISPR/Cas Genome Editing System and Its Application in Rice Improvement -- Rukmini Mishra, Satyabrata Nanda, and Raj Kumar Joshi -- Role of Genetic Engineering and Biotechnology as a Molecular Advance Tool and Trend in Quality Improvement of Rice Crop -- Aziz Ahmad, Deepak Kumar Verma, and Prem Prakash Srivastav -- Association Mapping in Rice: High Resolution Mapping Technique for Complex Traits -- Parmeshwar Kumar Sahu, Deepak Sharma, Vikash Kumar, Suvendu Mondal, Gautam Vishwakarma, and B. K. Das.
Includes bibliographical references and index.
Also available in print format.
Keywords: Rice -- Research; Rice -- Biotechnology; Rice -- Molecular aspects; TECHNOLOGY & ENGINEERING / Agriculture / General; Electronic books